Последний герой: Стихи. Песни. Воспоминания / сост. А. Корин - Цой Виктор Робертович (ЭКСМО, 2003)
Экземпляры: ЦБ (2003) / Инвентарный номер: 36276 / Цена: 56.10 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ц 76 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6